2017
DOI: 10.1007/s13744-017-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Development, Reproduction, Survival, and Demographic Patterns of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) on Different Commercial Tomato Cultivars

Abstract: The increase in the production of tomato, Solanum lycopersicon Mill. (Solanaceae), has favored the proliferation of pests, especially Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae). In this study, the development, reproduction, survival, and demographic parameters of T. absoluta reared on six commercial tomato cultivars (Cherry, Cordilheira, Giuliana, Nemoneta, Paron, and Santa Clara) were evaluated. Tuta absoluta completed its development in all tomato cultivars. Development from newly hatched caterpillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…The pest has the ability to grow and complete its developmental cycle on all tested varieties. A similar conclusion was drawn by Krechemer & Foerster (2017) with six different tomato varieties (namely Cherry, Cordilheira, Giuliana, Nemoneta, Paron, and Santa Clara). However, we found differences in the duration of embryonic development, larval stage duration, and pupal stage duration, resulting in a significant difference in the developmental cycle of T. absoluta on the different tomato varieties.…”
Section: Discussionsupporting
confidence: 84%
“…The pest has the ability to grow and complete its developmental cycle on all tested varieties. A similar conclusion was drawn by Krechemer & Foerster (2017) with six different tomato varieties (namely Cherry, Cordilheira, Giuliana, Nemoneta, Paron, and Santa Clara). However, we found differences in the duration of embryonic development, larval stage duration, and pupal stage duration, resulting in a significant difference in the developmental cycle of T. absoluta on the different tomato varieties.…”
Section: Discussionsupporting
confidence: 84%
“…In table 8, we summarized data for life-table parameters of T. absoluta and mirid predators when developing on tomato with T. absoluta as prey. Krechemer & Foerster (2017) determined the life table of T. absoluta on six commercial tomato cultivars at 20 ± 2°C, 70 ± 10% RH and 12 h photophase, among which the same cultivar we used, cv Santa Clara. The r m value varied from 0.09 for cv Santa Clara to 0.11 for cv Cherry.…”
Section: Discussionmentioning
confidence: 99%
“…20 reported that the r and R 0 values for S. cerealella were 0.077 to 0.115 days −1 and 17.17 to 44.09 eggs, respectively depending on the barley cultivar. The r and R 0 values for T. absoluta were 0.074 to 0.115 days −1 and 10.03 to 61.56 eggs, respectively, on different tomato cultivars 21,22 . The r of B. macroscopa was similar to several noctuid species, e.g ., in Helicoverpa armigera it was 0.115 to 0.142 days −1 and 0.171 to 0.264 days −1 in Spodoptera exigua (Hübner) 19,30 , but the R 0 values were less than those in H. armigera (177.3 to 270.1 eggs) and S. exigua (126.4 to 377.1 eggs) 17,30 .…”
Section: Discussionmentioning
confidence: 92%
“…Rostami et al . 21 reported the egg stage of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) lasted from 4.43 to 4.64 days on three tomato cultivars, but other researchers, found the egg stage ranged from 5 to 7 days in the species 22,23 , B. macroscopa also has a shorter pupal stage compared to T. absoluta . In our study, the B. macroscopa pupal stage ranged from 5 to 6 days, which was similar to the length reported under ideal temperatures for B. macroscopa 13 .…”
Section: Discussionmentioning
confidence: 99%